KINERJA INVESTASI PADA INDUSTRI PENGOLAHAN KELAPA TERPADU DI PROVINSI ACEH - Romano Romano (Jurnal Agrisep, 2011)
Investment Evaluation of Coconut Processing Industry in Aceh ProvinceABSTRACT. The needs for new processing technology that can utilize both by products and primary products such as coir and coconut shell become more important. This would increase the value-added level of coconut products in Aceh. Research has been conducted in four districts of Aceh Province and it has used census method. The results showed the coefficient of technology produced from 12 until integrated coconut processing industry is 0.6806. With an investment between Rp 342 million to Rp 825 million may produce values approximately Rp 1,543,707,300 to Rp 3,721,320,000 for 10 years industrial economic life. Efficiency of integrated technology still relatively produced low level of oil due to a number of factors and allocation of equipment investment. Furthermore, there are still residual values (salvage values) of coconuts that have not been exploited by employers.